Antibiotic resistance of hospital strains of Enterococcus faecalis and Enterococcus faecium - Mirović Veljko (Vojnosanitetski Pregled)
The aim of this study was to determine the resistance of Enterococcus faecalis (E. faecalis) and Enterococcus faecium (E. faecium) to penicillin, ampicillin, vancomycin, teicoplanin, gentamicin (high level), streptomycin (high level), oxytetracycline, chloramphenicol, rifampin, erythromycin, ciprofloxacin, norfloxacin, and nitrofurantoin from clinical specimens during 1999. The resistance of enterococci to antibiotics was determined by disk diffusion and dilution methods according to the American National Committee for Clinical Laboratory Standards guidelines. The production of β-lactamase was determined by nitrocefin disks. In E. faecalis and E. faecium isolates (n=111 and n=48) the frequency of the resistance to both penicillins was 0.9% and 89.6%, respectively. All enterococci isolates were β-lactamase negative. Only one strain of E. faecium was vancomycin resistant (Van A fenotype). Among E. faecalis isolates (n=109) high level gentamicin resistance (HLGR), high level streptomycin resistance (HLSR), and resistance to both agents was 52.3%, 50.4%, and 43.7%, respectively. Among E. faecium isolates (n=48) HLGR, HLSR, and to both agents were 68.7%, 75%, and 62.5% respectively. The majority of E. faecium isolates were resistant to both penicillin and ampicillin. E. faecalis remained susceptible to penicillins. Moreover, there was a very high incidence of enterococci resistant to high level aminoglycosides.